Development of an ultrasonic needle guide as an aid to percutaneous puncture of blood vessels - Kolb, Peter Joseph (Division of Biomedical Engineering, 2017)
The puncturing of blood vessels is often a "hit and miss" procedure which may take even a skilled physician considerable time to perform. Perhaps even more important than the time taken by medical personnel is the trauma inflicted on patients when the procedure is unnecessarily prolonged. A needle guide was developed, based on the well-known Doppler ultrasound principle. Two transducers, on sliding bars, are used to locate the vessel. A unique mechanical arrangement was devised for aiming the needle at the intersection point of the two ultrasonic beams. An account is given of the theory, engineering philosophy, design parameters and step-by-step development of the guide. Full mechanical and electronic drawings and photographs of the prototype also appear in this work.